Skrinning Fitokimia Ekstrak Daun Sirsak (Annona muricata) Dan Pengaruhnya Terhadap Laju Korosi Baja Karbon ST 37 - Leni Rumiyanti; Amilia Rasitiani; Ediman Giting Suka (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2019)
Research has been conducted on a phytochemical screening of soursop leaf extract (Annona muricata) and its effect on the corrosion rate of ST 37 carbon steel. Extraction of soursop leaves was carried out by the maceration method, while corrosion rate testing was carried out by weight loss method. ST 37 carbon immersion was carried out for 10 days with 7 variations of concentration, namely 0%, 5%, 10%, 15%, 20%, 25%, 30%, and 35%. The results of phytochemical screening showed that the soursop leaf extract contained saponins, triterpenoids, tannins, alkaloids, and flavonoids. The greatest corrosion rate was obtained at a concentration of 0%, which was 1.3 x 104 mm / y, while the lowest corrosion rate was at a concentration of 30%, which was 0.032 x 104 mm / y. The greatest corrosion inhibition efficiency occurred at a concentration of 35% at 97.53%. Based on the results of the reaserch, it can be concluded that the higher the concentration of soursop leaf extract used, the lower the corrosion rate and the higher the inhibition efficiency of the corrosion